Discover the Arjuna in You; An 18 Step Guid for Self-Awareness - "Modh, Satish" (Mumbai)
An 18 Step Guide for Self-Awareness DISCOVER ARJUNA. UNRAVEL THE REAL HERO IN YOU. Since time immemorial, Arjuna has come to embody strength, courage and valour. Legend has it that the great warrior from the epic tale Mahabharata, had excellent visual skills as demonstrated through the fabled Bird$1 (Bs Eye shot. The stories of his sharp-sightedness and heroism have spread far and wide. Each one of us have Arjuna$1 (Bs unwavering gaze to focus on our target and endeavour for the best. However, in our own lives, we are often unable to achieve our aims; we fail the allegorical Bird$1 (Bs Eye test. Discover the Arjuna in You, based on the teachings of the Bhagavad Gita, takes us through various phases of Arjuna$1 (Bs life. It engages in the deeply philosophical conversations between Krishna and Arjuna on life lessons, and inspires us to seek answers to our own predicaments. Once we break free from the clutches of our fears and inhibitions, we can empower ourselves through focus and determination and imbibe the values of the valiant Arjuna. Embark on a journey of motivation and become an unbeatable archer like Arjuna, because we too can set our targets, conquer every challenge along the way and emerge a winner. SATISH MODH has authored several pioneering books on disaster management. He is also the author of Ethical Management and The Care Revolution: A New Agenda for Resurgent India. He has published several research papers in reputed peer reviewed journals. He has developed a personality indicator based on Guna concept of the Bhagavad Gita. He has also conducted several workshops on leadership development for NGOs and business organizations based on this framework. s
Keywords: Psychology